Structural and functional myocardial abnormalities and arrhythmias in patients with type 1 diabetes complicated with ketoacidosis - N. V. Mukha; A. V. Govorin; D. N. Zajtsev; A. P. Filev (Российский кардиологический журнал)
Aim. To study the structural and functional cardiac changes and arrhythmias in patients with type 1 diabetes (T1D) complicated with ketoacidosis.Material and methods. We analyzed 24-hour Holter monitoring data in 112 patients with T1D complicated with diabetic ketoacidosis (DKA). To assess the left ventricular (LV) diastolic function, all patients underwent echocardiography.Results. In patients with T1D complicated with DKA, the following cardiac arrhythmias were recorded: supraventricular arrhythmias — 60,7%, premature ventricular contractions — 26,2%, premature ventricular and supraventricular contractions — 13,1%. In 30% of patients with T1D complicated with DKA, premature ventricular contractions were classified as class 4A, in 10% — class 4B. With severe DKA, 5% of patients had short runs of unstable ventricular tachycardia. As the severity of ketosis increases, myocardial remodeling and LV diastolic dysfunction are recorded, as well as the spectral and temporal parameters of heart rate variability decrease.Conclusion. In patients with T1D complicated with DKA, structural and functional LV abnormalities, the development of LV diastolic dysfunction and cardiac arrhythmias are more often recorded. The most pronounced changes were found in the group of patients with T1D with moderate and severe DKA.